Influence of organizational culture and job satisfaction on employee performance at the Gembor Periuk sub-district office Tangerang City - Sriwanti Pardosi; Herayati Herayati; Martinus Wahyu Purnomo (Junal Ilmu Manajemen, 2023)
Human resources are a driving factor in the running of organizational operations, the success of an organization is determined by the existence of its human resources. So that human resources or organizational employees become the main concern for achieving organizational success. Achieving these goals is influenced by several factors, namely organizational culture and job satisfaction. This researcher's approach uses an associative approach, with the aim of analyzing the problem of the relationship between one variable and other variables. Total sampling is taken from everything in the research. So the sample used in this research was 15 employees at the Gembor Periuk sub-district office, Tangerang City. Analysis methods, Quantitative Analysis, Classic Assumption Test, t Test, and F Test. Organizational culture influences employee performance at the Gembor Periuk Village Office, Tangerang City. This can be shown by the tcount value of 3.933 and ttable 1.78229. This means that tcount > ttable with a significant value of 0.002 < 0.05. Job satisfaction influences employee performance at the Gembor Periuk sub-district office. This can be shown by the tcount value of 3.125 and ttable 1.78229. This means that tcount > ttable with a significant value of 0.009 < 0.05. The influence of organizational culture and job satisfaction on employee performance at the Gembor Periuk sub-district office, this can be shown by the Fcount value of 12.632 and Ftable of 3.885. This means that Fcount > Ftable with a significant value of 0.001 < 0.05. The results of this research show that organizational culture and job satisfaction simultaneously have a positive and significant effect on employee performance at the Gembor Periuk Subdistrict Office.